Non-invasive brain stimulation and pain neuroscience education in the cognitive-affective treatment of chronic low back pain: Evidence and future directions - Alcon, Cory A.; Wang-Price, Sharon (Frontiers in Pain Research, 2022)
Chronic low back pain (CLBP) is among the leading causes of disability worldwide. Beyond the physical and functional limitations, people’s beliefs, cognitions, and perceptions of their pain can negatively influence their prognosis. Altered cognitive and affective behaviors, such as pain catastrophizing and kinesiophobia, are correlated with changes in the brain and share a dynamic and bidirectional relationship. Similarly, in the presence of persistent pain, attentional control mechanisms, serving to organize relevant task information, are impaired. These deficits demonstrate that pain may be a predominant focus of attentional resources, leaving limited reserve for other cognitively demanding tasks. Cognitive dysfunction may limit one’s capacity to evaluate, interpret, and revise the maladaptive thoughts and behaviors associated with catastrophizing and fear. As such, interventions targeting the brain and resultant behaviors are compelling. Pain neuroscience education (PNE), a cognitive intervention used to reconceptualize a person’s pain experiences, has been shown to reduce pain catastrophizing and kinesiophobia. However, cognitive deficits associated with chronic pain may impact the efficacy of such interventions. Non-invasive brain stimulation (NIBS), such as transcranial direct current stimulation (tDCS) or repetitive transcranial magnetic stimulation (rTMS) has been shown to be effective in the treatment of anxiety, depression, and pain. In addition, as with treatment of most physical and psychological diagnoses, an active multimodal approach is considered optimal. Therefore, combining the neuromodulatory effects of NIBS with a cognitive intervention such as PNE could be promising. This review highlights the cognitive-affective deficits associated with CLBP while focusing on current evidence for cognition-based therapies and NIBS.